The Impact of Resection Margins in Primary Resection of High-Grade Soft Tissue Sarcomas: How Far Is Far Enough? - Julian Miles Steffens; Tymoteusz Budny; Georg Gosheger; Marieke De Vaal; Anna Maria Rachbauer; Andrea Laufer; Nina Myline Engel; Niklas Deventer (Biomedicines)
Background/Objectives: The World Health Organization’s (WHO) classification of tumors contains around 80 entities of soft tissue sarcomas (STSs). Currently, surgery is the standard treatment for patients with localized STS, but the adequacy of resection margins in soft tissue sarcomas (STSs) remains a topic of intense discussion. Methods: This single-center study retrospectively reviewed 203 patients with primary high-grade soft tissue sarcoma, including a follow-up period of at least 24 months. Patients with prior resection, secondary STS, metastasis at presentation, or those who required amputational surgery were excluded from the study. Patients were categorized based on their margin thickness: positive (n = 13, 6.4%), 0–1 mm (n = 67, 33.0%), 1–5 mm (n = 70, 34.5%), and >5 mm (n = 27, 13.3%). Results: A total of 64 out of 203 (31.5%) patients developed a local recurrence. The estimated 5-year local-recurrence-free survival (LRFS) was 11.5% (CI 4–25%) for positive margins, 58% (CI 51–64%) for margins 0–1 mm, 76% (CI 70–81%) for margins > 1–5 mm, and 93% (CI 88–98%) for margins > 5 mm. No local recurrences occurred in patients with margins > 5 mm and adjuvant radiotherapy. Margin status significantly influenced the development of distant metastasis and overall survival. Adjuvant radiotherapy improved both local control and overall survival. Conclusions: To minimize the risk of local recurrence (LR), a resection margin greater than 5 mm should be attained. When adjuvant radiotherapy is applied, the likelihood of LR decreases even more. In scenarios where preserving critical structures is essential, a resection margin of less than 5 mm can be acceptable for ensuring local control.